Euripidés Médeiájának magyar fordításairól - Polgár, Anikó (Studia Litteraria, 2017)
This study is dealing with two Hungarian translations of Euripides’ Medea. The translation made by Grácia Kerényi was produced in the second half of the 20th century, whereas the version by Zsuzsa Rakovszky was published at the beginning of the 21st. The difference between the translations regarding their textual strategies, the professional background of the translators and the final goal of the works is abysmal. Grácia Kerényi was an expert of ancient literatures, her translation was published in the official and renowned collection of Euripides’ work, Zsuzsa Rakovszky on the other hand translates predominantly from English, and her version was inspired by the request of the theatre. The study contains three parts: in the first the author analyses Kerényi’s Medea in the context of the philological reconstruction, in the second, the author examines the same text modified and revised by Fruzsina Magyar, who was the dramatic advisor of the theatre performance in Szolnok, and the third part reflects on the problems of validity, poetical force and immediacy in the translation of Zsuzsa Rakovszky.